2015
DOI: 10.1016/j.parkreldis.2015.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic changes in the mesolimbic pathway in Parkinson's disease motor subtypes

Abstract: Background Parkinson’s disease (PD) is a common neurodegenerative disorder associated with gray matter atrophy. Cortical atrophy patterns may further help distinguish between PD motor subtypes. Comparable differences in subcortical volumes have not been found. Methods Twenty-one cognitively intact and treated PD patients, including 12 tremor dominant (TD) subtype, Nine postural instability gait dominant (PIGD) subtype, and 20 matched healthy control subjects underwent 3.0 Tesla high-resolution structural MRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 16 publications
1
25
1
Order By: Relevance
“…Damage of the nucleus accumbens has also been reported in PD patients. Atrophy of this structure has been associated with cognitive impairment and chronic dopaminergic treatment . Our patients were not only drug‐naïve, but also did not show any sign of cognitive impairment, which could explain the lack of detected differences in the accumbens.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Damage of the nucleus accumbens has also been reported in PD patients. Atrophy of this structure has been associated with cognitive impairment and chronic dopaminergic treatment . Our patients were not only drug‐naïve, but also did not show any sign of cognitive impairment, which could explain the lack of detected differences in the accumbens.…”
Section: Discussionmentioning
confidence: 62%
“…Very recently, several studies have applied shape analysis to patients with PD, but results are inconsistent. Of these, only one study targeted drug‐naïve patients, whereas the others dealt with patients undergoing medications, either cognitively normal or showing cognitive deficits or apathy …”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with the idea that in the PD-like brain state, where striatal regions are dopamine-deafferented, motor improvement afforded by dopamine agonists are acting on upregulated postsynaptic dopamine receptors to rapidly provide more normal function of striatal outflow to downstream motor structures. The limbic brain regions involved in ICDs are largely intact in PD [39] (but see [40,41]) and in rats with 6OHDA-induced lesions of the DLS [10,13], and Dopamine agonist therapy for PD may serve to over activate limbic dopamine receptors. Furthermore, chronic exposure to PPX upregulates D3R [42].…”
Section: Discussionmentioning
confidence: 99%
“…An additional limitation of previous studies is that while atrophy of the hippocampus and related medial temporal lobe cortex are reported as common features in PD (7, 8, 19, 20), morphometric studies have either not addressed (11, 13, 16, 17) or found (3, 12, 14, 15, 18, 21) hippocampal shape differences.…”
Section: Introductionmentioning
confidence: 99%